2022
DOI: 10.22495/rgcv12i3p4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 effects on the going concern audit opinion in MENA region: Text mining approach

Abstract: The COVID-19 pandemic has affected the economic sector, especially the audit task that requires the physical intervention of the auditor. The aim of this paper is to study the effect of COVID-19 on audit opinion in the MENA region through a novel text mining approach. The collected data included 83 bank reports from 377 branches in 14 MENA countries. The text mining approach was employed using Python software via corpus creation, tokenization, stop words removal, stemming, and feature selection. Afterwards, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Study (Feliciano, 2001) This study is one of the studies that confirmed the existence of a positive relationship between trade openness and employment, at least in the long run, as it is expected that the process of trade liberalization will lead to the contraction of some sectors and the expansion of others, but the problem stems from the fact that it can The process of expansion proceeds at a slower rate compared to the process of deflation. As for the study of (Hoekman, 2005), this study indicated that there is a positive relationship between trade openness and employment in the long term, and that trade liberalization leads to the contraction of some economic sectors and the expansion in other sectors, and that the expansion process taking place It has a weak path compared to the speed of the downturn in other economic sectors, according to the study of the World Bank (Feghali et al, 2022). Which indicated that trade is a major driver of growth and the reduction of unemployment and poverty, especially in developing countries.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Study (Feliciano, 2001) This study is one of the studies that confirmed the existence of a positive relationship between trade openness and employment, at least in the long run, as it is expected that the process of trade liberalization will lead to the contraction of some sectors and the expansion of others, but the problem stems from the fact that it can The process of expansion proceeds at a slower rate compared to the process of deflation. As for the study of (Hoekman, 2005), this study indicated that there is a positive relationship between trade openness and employment in the long term, and that trade liberalization leads to the contraction of some economic sectors and the expansion in other sectors, and that the expansion process taking place It has a weak path compared to the speed of the downturn in other economic sectors, according to the study of the World Bank (Feghali et al, 2022). Which indicated that trade is a major driver of growth and the reduction of unemployment and poverty, especially in developing countries.…”
Section: Literature Reviewmentioning
confidence: 89%